2022
DOI: 10.1108/ijoa-07-2022-3350
|View full text |Cite
|
Sign up to set email alerts
|

How social interaction can prevent interpersonal conflict from inducing turnover intentions and diminishing championing behaviour

Abstract: Purpose The purpose of this study is to draw from conservation of resources theory to examine how employees’ experience of resource-draining interpersonal conflict might diminish the likelihood that they engage in championing behaviour. Its specific focus is on the mediating effect of their motivation to leave the organization and the moderating effect of their peer-oriented social interaction in this connection. Design/methodology/approach The research hypotheses are empirically assessed with quantitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Empowering leadership enhances team members' emotional climate and well-being, fostering collaboration, mutual respect, and open communication (Rudolph et al, 2022). However, research suggested that interpersonal conflict can be a stressor that may undermine the positive effects of empowering leadership on team members (De Clercq & Belausteguigoitia, 2022;Spânu et al, 2013) and how leaders manage conflicts, could significantly shape the team's emotional climate (Yin et al, 2022).…”
Section: Empowering Leadershipmentioning
confidence: 99%
“…Empowering leadership enhances team members' emotional climate and well-being, fostering collaboration, mutual respect, and open communication (Rudolph et al, 2022). However, research suggested that interpersonal conflict can be a stressor that may undermine the positive effects of empowering leadership on team members (De Clercq & Belausteguigoitia, 2022;Spânu et al, 2013) and how leaders manage conflicts, could significantly shape the team's emotional climate (Yin et al, 2022).…”
Section: Empowering Leadershipmentioning
confidence: 99%